Tourism Perceptions and Subjective Well-Being: Insights from GIAHS Sites - Jie Yang; Shi‑Zheng Huang; Onanong Cheablam (Journal of Human, Earth, and Future)
The subjective well-being (SWB) of residents serves as a crucial measure of social harmony. This study applied the cognition-affection-behavior theory to investigate how tourism perceptions influence residents’ SWB while also assessing the intermediary roles of emotional solidarity (ES) and resident-tourist value co-creation (RVC). Researchers collected 411 valid survey responses from residents in GIAHS and utilized Structural Equation Modeling path analysis and bootstrapping method to test the proposed hypotheses. The results indicate that benefit perceptions positively impact residents’ SWB, with ES and RVC serving as sequential mediators in this relationship. In GIAHS, improving residents' perception of benefits can foster ES and RVC, creating a connection between residents and tourists and ultimately enhancing residents' SWB.